Pentameric C-reactive protein is a better prognostic biomarker and remains elevated for longer than monomeric CRP in hospitalized patients with COVID-19 - Hopkins, Francis R.; Nordgren, Johan; Fernandez-Botran, Rafael; Enocsson, Helena; Govender, Melissa; Svanberg, Cecilia; Svensson, Lennart; Hagbom, Marie; Nilsdotter-Augustinsson, Åsa; Nyström, Sofia; Sjöwall, Christopher; Sjöwall, Johanna; et al. (Frontiers in Immunology, 2023)
The differing roles of the pentameric (p) and monomeric (m) C-reactive protein (CRP) isoforms in viral diseases are not fully understood, which was apparent during the COVID-19 pandemic in the understanding of the clinical course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Herein, we investigated the predictive value of the pCRP and mCRP isoforms for COVID-19 severity in hospitalized patients and evaluated how the levels of the protein isoforms changed over time during and after acute illness.This study utilized samples from a well-characterized cohort of Swedish patients with SARS-CoV-2 infection, the majority of whom had known risk factors for severe COVID-19 and required hospitalization.The levels of pCRP were significantly raised in patients with severe COVID-19 and in contrast to mCRP the levels were significantly associated with disease severity. Additionally, the pCRP levels remained elevated for at least six weeks post inclusion, which was longer compared to the two weeks for mCRP.Our data indicates a low level of inflammation lasting for at least six weeks following COVID-19, which might indicate that the disease has an adverse effect on the immune system even after the viral infection is resolved. It is also clear that the current standard method of testing pCRP levels upon hospitalization is a useful marker for predicting disease severity and mCRP testing would not add any clinical relevance for patients with COVID-19.